Colonic metastases from carcinoma of the lung, an unusual presentation. Case report and literature review (2018)
The symptomatic metastasis of the colon from a pulmonary cancer is rare; however, the global incidence of pulmonary cancer is 12.9%. It is an infrequent site of metastasis, with a prevalence of less than 0.5% in patients with pulmonary cancer. One of the most common manifestation is intestinal obstruction. We present a case report of a patient with an acute lower intestinal bleeding from multiple metastasis lesion of the colon as the initial manifestation of a non-small cell lung carcinoma.